Brosch AI - Distorted Dreams: Expanding and Animating an Archive With AI - Wolfersberger, Victoria; Pham, Celine; Abasolo, Jolanda; Hagler, Juergen (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
Brosch AI - Distorted Dreams explores the intersection of artificial intelligence, art, archives, and animation. The project transforms the archive of Upper Austrian artist Klemens Brosch (1894– 1926) into an AI-animated film. While AI image-generation tools typically rely on online archives, museum collections often provide only lowquality digital reproductions. By utilizing high-resolution images from Brosch’s archive, this project investigates the potential of AI-driven animation while addressing challenges related to stylistic control, and creative authenticity. The findings demonstrate that while AI can produce high-quality outputs, extensive refinement and iterative adjustments are necessary to preserve the essence of Brosch’s work. The project sparks critical discussions on authorship, originality, and the evolving role of technology in artistic creation.